2002
DOI: 10.1002/path.1053
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of key cell‐cycle checkpoint proteins in colorectal tumours

Abstract: Aberrations in the components of cell-cycle checkpoints are a common feature of many tumours and several have been shown to have prognostic significance in colorectal cancer. In this study, seven components of cell-cycle control [cyclin D1, retinoblastoma (pRb), p21, p27, p16, p53, and proliferating cell nuclear antigen (PCNA)] were examined in a large series of well-characterized colorectal adenocarcinomas using immunohistochemistry to ascertain co-regulation and influence on survival. The majority (92%) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 54 publications
8
70
3
Order By: Relevance
“…In this study, we have shown that low levels of cyclin D1 and p27 correlated to poor prognosis in conventional RCC using univariate analysis, and that p27 remained significantly associated to survival in the multivariate analyses. The association between low cyclin D1 and poor prognosis in the univariate analysis agrees with the data reported for breast cancer (Gillet et al, 1996;Nielsen et al, 1997;Hwang et al, 2002;McKay et al, 2002), although an association between high cyclin D1 and poor prognosis has been reported in many malignancies (Å kervall et al, 1997;Gansauge et al, 1997).…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we have shown that low levels of cyclin D1 and p27 correlated to poor prognosis in conventional RCC using univariate analysis, and that p27 remained significantly associated to survival in the multivariate analyses. The association between low cyclin D1 and poor prognosis in the univariate analysis agrees with the data reported for breast cancer (Gillet et al, 1996;Nielsen et al, 1997;Hwang et al, 2002;McKay et al, 2002), although an association between high cyclin D1 and poor prognosis has been reported in many malignancies (Å kervall et al, 1997;Gansauge et al, 1997).…”
Section: Discussionsupporting
confidence: 86%
“…PCNA is expressed in cycling cells and is used frequently to measure the proliferative activity of tissues (28). In addition, it is the most frequently observed protein among cell cycle -associated proteins (29). The PCNA promoter contains two CCAAT boxes at nucleotides À95 and À145 (30).…”
Section: Fig 2 Cytoplasmic Expression Of the Cyclin B2 Proteinmentioning
confidence: 99%
“…Biotinylated goat anti-mouse secondary antibody, a complex of avidin with horseradish peroxidase (HRP) and diaminobenzidine (DAB) were used as the detection-staining system. The cellular localisation of L-FABP immunoreactivity was determined and scored for both intensity (negative, weak, moderate and strong) and proportion (0, 1 -5, 6 -25, 26 -50, 51 -75 and 76 -100%) of stained cells as previously described (Leeman et al, 2002;McKay et al, 2002). To allow comparison of L-FABP immunostaining with pathological stage and survival for each cancer integer values were assigned to the scores of intensity (0 -3) and proportion of tumour cells stained (0 -5).…”
Section: Immunohistochemistrymentioning
confidence: 99%